2000
DOI: 10.1080/080352500300002633
|View full text |Cite
|
Sign up to set email alerts
|

Severe adenovirus bronchiolitis in children

Abstract: Adenovirus can cause severe bronchiolitis in previously healthy children. Diagnosis may be difficult to achieve. The role of antiviral therapy in the treatment of adenoviral infections remains to be cleared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In situ hybridization showed that alveolar and bronchiolar epithelial cells are infected by adenovirus in pneumonias [15] (Figure 2). Other less common respiratory consequences of adenovirus infection reported in this age group include bronchiolitis [14,16,17], post-infectious bronchiolitis obliterans [18 ] and, when combined with or preceded by measles infection, bronchiectasis [19,20].…”
Section: Pediatric Populationmentioning
confidence: 99%
“…In situ hybridization showed that alveolar and bronchiolar epithelial cells are infected by adenovirus in pneumonias [15] (Figure 2). Other less common respiratory consequences of adenovirus infection reported in this age group include bronchiolitis [14,16,17], post-infectious bronchiolitis obliterans [18 ] and, when combined with or preceded by measles infection, bronchiectasis [19,20].…”
Section: Pediatric Populationmentioning
confidence: 99%
“…Adenoviruses cause a broad spectrum of clinical disease, including respiratory tract infection, pharyngoconjunctival fever, conjunctivitis, hemorrhagic cystitis, and gastroenteritis. Although most infections are self-limited, adenoviruses have been associated with severe and even fatal infections in both immunocompromised and healthy individuals (6,22,27). In the immunocompromised host, adenovirus can cause severe localized disease or disseminated disease with multiorgan failure (2,11).…”
mentioning
confidence: 99%
“…6 Although most infections are self-limited, ADV can be associated with severe or lethal infection in both immunocompromised and healthy individuals. [7][8][9][10] In clinical practice, ADV may be underdiagnosed. Isolation of ADV from cell culture is quite sensitive, but results take several days, limiting clinical utility.…”
mentioning
confidence: 99%